THE BIDIRECTIONAL RELATIONSHIP BETWEEN STRESS AND PSYCHOPATHOLOGY: REVISITING THE STRESS GENERATION HYPOTHESIS (Annual of the Faculty of Philosophy in Skopje, 2025)
For more than three decades, the stress generation hypothesis has inspired indepthstudy of the relationship between psychopathological phenomena and stressfulexperiences. The model proposes that in individuals already struggling with significantmental health problems, certain personality, cognitive, and interpersonal vulnerabilityfactors lead to experiencing a higher rate of stressful life events. Initially, the hypothesiswas proposed in relation to depression, but it was later associated with other mental disordersas well. Unlike dominant assumptions about the relationship between stress andpsychopathology, this model highlights the active role that individuals play in shapingtheir life circumstances. This generated, so-called, dependent stress is both an outcome(at least partly) of impaired mental health, as well as a mechanism that maintains orexacerbates psychological dysfunctions. The paper presents a brief review of empiricalfindings that support the transdiagnostic utility of the model and provide insight intorisk factors for stress generation. Clinical implications relevant to the treatment of impairedmental health are discussed, along with methodological limitations and recommendations,as well as directions for future research.
Keywords: stress generation; dependent stressors; psychopathology; transdiagnostic